Pupils who communicate well know how to resolve their personal conflicts (Journal of Parents and Teachers, 2026)
This article includes some excerpts from a programme produced by the Fundación Encuentro entitled ‘Violence in Schools’. This programme was commissioned, out of concern, by the Council of Europe in response to the conflicts that frequently arise in schools, both at primary and secondary level. The programme referred to in this article is aimed at language teachers in the first cycle of secondary education, with the aim of developing listening and speaking skills, conveying constructive messages and fostering cooperation. It consists of seven stages described throughout the article.
Keywords: school violence; listening; constructive feedback; communication; cooperation